Hexa Helix Framework on the Dynamics of the Indonesian Halal Fashion Industry - Yeni Windriasih; Wily Mohammad; Besar Agung Martono (Jurnal Ilmiah Manajemen Ekonomi Dan Akuntansi (JIMEA), 2023)
This qualitative research delves into Indonesia's Halal Fashion industry, employing a descriptive approach and relying on extensive secondary data collected from diverse sources such as scientific articles, publications, reports, and industry papers. Utilizing the Hexa Helix Stakeholder Concept as a guiding framework, the study aims to unravel the industry's nature, challenges, and potential while analyzing the roles and interactions of stakeholders—government institutions, affected communities, NGOs, businesses, mass media, and universities. Employing thematic and content analysis, the research seeks to unearth recurring patterns and stakeholder dynamics, offering insights into the complexities of the Halal Fashion landscape in Indonesia. Ultimately, this study advocates for collaborative stakeholder efforts, emphasizing the interdependence among these sectors for the industry's growth, ethical practices, and innovation within Indonesia's evolving market setting. The study's findings underscore the importance of addressing multifaceted challenges both externally and internally through collective stakeholder efforts among government, industry, academia, civil society, media, and culture, essential in navigating the industry towards sustained growth and viability.